Maqasid al-Sharia dalam Waris Matrilineal: Analisis Fatwa Ulama Perempuan Minangkabau Berdasarkan Prinsip ABS SBK - Zulfaqar Syah Rafsanjani; Vicka Wulandari; Rispiyanti Siti N; Cesya Hanifa Febryerko; Muhamad Parhan (Akhlak : Jurnal Pendidikan Agama Islam dan Filsafat, 2025)
This research examines the matrilineal inheritance system in Minangkabau society through the perspective of maqasid al-sharia and the principles of Adat Basandi Syarak, Syarak Basandi Kitabullah (ABS-SBK). The matrilineal inheritance system which transmits inheritance through the mother's lineage is considered controversial in relation to Islamic law which is based on faraid. Through a qualitative approach using literature study and interview methods, this research analyzes the fatwas of Minangkabau female clerics which emphasize that the customary system can be in harmony with the main objectives of Islamic law, such as the protection of life, offspring, property and religion. The results show that female ulama see this system as a form of contextual ijtihad that considers justice and social benefit. The distinction between high inheritance (custom) and search property (divided according to Islamic law) reflects the flexibility in combining adat and sharia. Therefore, the Minangkabau matrilineal inheritance system is not only considered valid according to custom, but is also relevant to maqasid al-sharia.